Conceptual Understanding Of Amlapitta W.S.R. To GERD: A Review Article - Sharma, Rahul Kumar (International Research Journal of Ayurveda & Yoga, 2021)
One of the most common gastrointestinal illnesses is gastro esophageal reflux disease (GERD). GERD is a clinical condition defined by the presence of gastro esophageal reflux (GER) via the lower esophageal sphincter (LES) into the esophagus or oropharynx, resulting in symptoms, esophageal tissue damage, or both. Retrosternal searing sensation (heart burn), epigastric discomfort (often extending to the back), and regurgitation are the traditional trio of symptoms. It is difficult to find a direct link between GERD and Ayurvedic nomenclature. Doshadushya-Sammurchhna conferment and Samprapti should be examined. Aggravated Vata Dosha is responsible for Vishama Gati (motor irregularities) in Annavaha Srotas, which leads to Pitta deracination from its native location. It is difficult to distinguish between situations such as Amashayagata Vata, Amlapitta, Pitta Vriddhi, Sama Pitta, and Vidagdhajirna. This review will give a better knowledge of etiopathogenesis, as well as a therapeutic method for managing patients by breaking the pathogenesis chain (Samprapti Vighatana). Diagnostic and therapeutic advances have enhanced our capacity to recognize and manage illness consequences. In this section, we explore the etiology and consequences of GERD, as well as the therapeutic treatment to this prevalent condition.